Optoelectronic properties of 3-acetyl-6-bromocoumarin compound in various solvents and concentrations - Kurt, Adnan; Gunduz, Bayram; Ilter, Zulfiye; Koca, Murat (Academic Publication Council, 2019)
In present study, the optoelectronic parameters of a coumarin-derived compound, 3-acetyl-6-bromocoumarin (ABRC), were studied for various solvents and concentrations. The investigated parameters were absorbance band edge, mass extinction coefficient, optical band gap, refractive index, real and imaginary parts of complex dielectric constant, incidence and refraction angle, contrast, optical and electrical conductance. The optical band gap values of 3-acetyl-6-bromocoumarin in DMF and DMSO solvents were found to be 3.110 eV and 3.092 eV at the same concentration of 120 mu M, respectively. In addition, the optical band gap decreased from 3.151 to 2.823 eV with increasing concentration from 27 mu M to 23 mM. The refractive indices of compound are discussed in detail using Herve-Vandamme, Kumar-Singh, Moss, Ravindm and Reddy methods. A comparative analysis of the results is presented . The results showed that the ABRC material exhibited semiconductor behavior and might be used in optoelectronic devices such as diodes and sensors.
Keywords: Coumarin; optoelectronic properties; optical and electrical conductance; semiconductor; solvent and concentration effect